'Imperfect' conjugated polymer nanoparticles from MEH‐PPV for bioimaging and Fe(III) sensing. (3rd October 2014) - Xu, Jingyi; Zhou, Ying; Cheng, Guifang; Liu, Shuxian; Dong, Meiting; Huang, Chaobiao
Abstract A simple and effective method was reported for the preparation from MEH‐PPV of conjugated polymer nanoparticles (Pdots) that are water‐soluble and well dispersed. The as‐prepared Pdots show bright orange fluorescence at a quantum yield up to 32.37%. The fluorescence intensity of Pdots can be quenched with good selectively by the successive addition of Fe3+. In addition, the as‐obtained Pdots were applied to the imaging of HeLa cells, and exhibited low cytotoxicity and excellent biocompatibility. Copyright © 2014 John Wiley & Sons, Ltd.